2018
DOI: 10.3791/57688
|View full text |Cite
|
Sign up to set email alerts
|

Generation of First Heart Field-like Cardiac Progenitors and Ventricular-like Cardiomyocytes from Human Pluripotent Stem Cells

Abstract: The generation of large amounts of functional human pluripotent stem cells-derived cardiac progenitors and cardiomyocytes of defined heart field origin is a pre-requisite for cell-based cardiac therapies and disease modeling. We have recently shown that Id genes are both necessary and sufficient to specify first heart field progenitors during vertebrate development. This differentiation protocol leverages these findings and uses Id1 overexpression in combination with Activin A as potent specifying cues to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Since PGC1/PPARα signals promoted CM contractility, we next sought to identify genes mediating the process. To do this, we selected 148 genes significantly downregulated in p7 PGC1 cmKO CMs (Table S2) and performed a single-cell highthroughput functional assay with PSC-CMs [36][37][38] treated with PPARα-specific ligands (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Since PGC1/PPARα signals promoted CM contractility, we next sought to identify genes mediating the process. To do this, we selected 148 genes significantly downregulated in p7 PGC1 cmKO CMs (Table S2) and performed a single-cell highthroughput functional assay with PSC-CMs [36][37][38] treated with PPARα-specific ligands (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Animals and PSC Culture. PGC1α/β flox, Ai9, Yap1flox mice (Lai et al, 2008;Lin et al, 2004;Madisen et al, 2010;Zhang et al, 2010) were obtained from the Jackson Laboratory. All protocols involving animals followed U.S NIH guidelines and were approved by the animal and care use committee of the Johns Hopkins Medical Institutions.…”
Section: Methodsmentioning
confidence: 99%
“…Since PGC1/PPARα signals promoted CM contractility, we sought to identify downstream genes regulating calcium han-dling. To do this, we performed a single-cell high-throughput functional assay with PSC-CMs (Cunningham et al, 2017;McKeithan et al, 2017;Yu et al, 2018) treated with PPARαspecific ligands as shown in Figure 6A. Single cell analysis of calcium handling revealed that ligand-treated PSC-CMs have shorter ( 30ms) calcium transient duration (CTD) as compared to vehicle treated cells (DMSO) ( Figure 6B and Figure 6C).…”
Section: Pgc1/pparα Signaling Promotes CM Maturation By Regulating Kementioning
confidence: 99%
“…hiPSC-derived cardiomyocytes were produced as previously described. 23, 24 Cardiomyocytes were plated in 384 wells and transfected with siRNAs (see Online Appendix). Two days after transfection, EdU was added to the media for 24 hours and fixed.…”
Section: Methodsmentioning
confidence: 99%